Analysis of Link Popularity among the Nepal Governments’ Websites by using HITS Algorithm - Bhandari, Bhim; Ram Joshi, Dr. Shashidhar (IJRDO -Journal of Computer Science Engineering, 2017)
New innovations in science and technology, communication becomes faster and easier. Information dissemination tools become the URLs through internet. Nepal Government has taken major initiatives and has good impact for g-governance. In this context, a close study among the governmental organizations’ URLs and their links from one web page to another helps for information dissemination. A web page’s link popularity is measured by the number of other web pages that link to it, and links from pages on other web sites. The page popularity is measured by using HITS and PageRank methods. The two main factors relevance and reputation are considered as major findings during study. Relevance is a measure of how easy it is for the search engine to tell that your web page is really about the search term that’s been used. It improves relevance with on-page search engine optimization, and talks about that extensively on other pages of our site. Reputation is measured by the number of links coming into one web site and the quality of those links. The most common term for that is "link popularity". Keyword formulation and link definition in the government web sites is random thus status of link popularity is weak. Out of twenty-nine web sites on five websites have implemented the concept of the inlink and outlink i.e. relevancy is better